Effects of private caregivers on nutritional risk and anxiety in stroke survivors with dysphagia: an observational study - Zhao, Weijia; Zeng, Jing; Li, Shuaiqi; Chen, Sheju (Frontiers in Nutrition, 2025)
BackgroundPrivate caregivers are common in developing countries as supplements to healthcare human resources. However, the effects of private caregivers on inpatient conditions remain unclear. This study explored the effect of private caregivers on nutritional risk and anxiety in patients with dysphagia after ischemic stroke.MethodsThis observational study included patients with dysphagia after ischemic stroke between 2022 and 2024 in central China. Participants were divided into non-caregiver and private caregiver groups. A single-factor analysis was used to explore the differences between the baseline assessments of the two groups. We then used propensity score matching (PSM) to balance significant baseline variables, including anxiety at admission, and demographic and clinical characteristics. In the matched sample, we used the average treatment effect on the treated (ATT) to uncover the influence of the patient groups on nutritional risks and anxiety on day 10.ResultsA total of 2,234 patients were included, and there were 766 cases in the private caregiver group. Before PSM, there were significant reductions in anxiety (47.00 vs. 32.86%, P < 0.001) and nutritional risks (100.00 vs. 70.55%, P < 0.001) from days 1 to 10. After PSM, there were no significant differences in any baseline assessments, and 766 pairs of cases were successfully captured. The ATT analysis showed that before and after PSM, there was no significant correlation between groups and nutritional risks (30.75 vs. 29.41%, P = 0.573), but there was a significant correlation between groups and anxiety on day 10 (34.89 vs. 23.40%, ATT = 0.234 after matching, P < 0.001).ConclusionsPrivate caregivers can effectively reduce anxiety in hospitalized patients with dysphagia following ischemic stroke, but they do not have a significant impact on nutritional risks.